Maternal hepatic immunology during pregnancy - Yang, Ling; Meng, Yao; Shi, Yuxiang; Fang, Hongxu; Zhang, Leying (Frontiers in Immunology, 2023)
The liver plays pivotal roles in immunologic responses, and correct hepatic adaptations in maternal immunology are required during pregnancy. In this review, we focus on anatomical and immunological maternal hepatic adaptations during pregnancy, including our recent reports in this area. Moreover, we summarize maternal pregnancy-associated liver diseases, including hyperemesis gravidarum; intrahepatic cholestasis of pregnancy; preeclampsia, specifically hemolysis, elevated liver enzymes, and low platelet count syndrome; and acute fatty liver of pregnancy. In addition, the latest information about the factors that regulate hepatic immunology during pregnancy are reviewed for the first time, including human chorionic gonadotropin, estrogen, progesterone, growth hormone, insulin like growth factor 1, oxytocin, adrenocorticotropic hormone, adrenal hormone, prolactin, melatonin and prostaglandins. In summary, the latest progress on maternal hepatic anatomy and immunological adaptations, maternal pregnancy-associated diseases and the factors that regulate hepatic immunology during pregnancy are discussed, which may be used to prevent embryo loss and abortion, as well as pregnancy-associated liver diseases.